THE EFFECTS OF LEADERSHIP STYLES ON ENABLING TEAM EFFECTIVENESS FOR MULTIPLE TEAM MEMBERSHIPS - Mntambo, Nokukhanya; Chan, Kai-Ying (The South African Journal of Industrial Engineering, 2024)
The prevalence of multiple team membership (MTM) in the modern organisation results from the need of an organisation to be efficient with its resources so that the desired efficiency is achieved. This study investigates the effect of leadership styles (transactional, transformational, directive, and laissez-faire) on enabling team effectiveness in the context of MTM. The team effectiveness criteria used are team viability, team processes, and quality of group experience. The data was collected through online questionnaires from 53 individuals in a mining organisation. The results showed a positive relationship between the transactional leadership style and all three criteria of team effectiveness, whereas the directive leadership style indicated a negative relationship with those criteria. Transformational leadership showed a positive impact only on the quality of group experience. Based on the results, it is recommended that transactional leadership styles be adopted for team effectiveness in the context of MTM for similar organisations.